Nurses as therapeutic agents in the extreme environment of the desert war, 1940–44. (23rd July 2015) - Brooks, Jane
Abstract Aims The purpose of this article is to explore therapeutic nursing with combatants in the extreme environment of the desert in World War II. Background The notion of nursing as therapy gained credence in the 1990s and is currently experiencing resurgence, as nurses seek to find meaning in their work and improve patient care in the post‐Francis environment. Design This discussion paper will use the hostile space of the desert war zone in World War II to explore nurses' therapeutic engagement with their combatant patients. It will examine how nurses provided care and comfort through the use of self, fundamental nursing skills, improvisation and innovation and the manipulation of the environment. Data sources The data used are a combination of letters, diaries, memoirs and published archival material. Much of the personal testimony is part of an uncatalogued archive of correspondence between nurses and the Matron‐in‐Chief of the Queen Alexandra's Imperial Military Nursing Service. Implications for nursing Nurses sometimes struggle to identify the importance of their work, compared with other members of the multidisciplinary team. By understanding nursing as therapy, the profession can articulate how their work is fundamental to the healing, or support to a dignified death of their patients. This article illustrates how the therapeutic engagement with patients, even in the most difficult of environments, is possible and brings comfort. Conclusion Deserts are among the most hostile of any space inhabited by people. Yet, even in a place where survival is difficult, therapeutic nursing can support healing and recovery.